Global health education in Chinese universities and potential for collaboration with schools of nursing: A qualitative study - Quanlei Li; Stephen Gloyd; Dong Xu; Yan Hu; Huaping Liu; Sarah Gimbel (Elsevier, 2017)
Background: The Chinese Consortium of Universities for Global Health (CCUGH) was established within schools of public health in 2013 with the goal of enhancing global health in China. Expanding nursing students' exposure to global health curricula is important as nurses are essential actors in the health care system. However, information related to existing global health education within CCUGH-affiliated universities and the current engagement of Chinese schools of nursing in global health remains extremely limited. Objective: To identify and describe the current definitions and conceptualizations of global health education in Chinese universities, with a focus on schools of nursing, in order to explore potential opportunities for strengthened collaboration between global health initiative and schools of nursing in China. Methods: Purposive sampling with snowballing was used to recruit 19 key informants who were critical stakeholders in global health and nursing in China. Key informant interviews were conducted from July 2014 to February 2015, and data were updated in June 2016. Content analysis was used to analyze data via Atlas.ti 7. Results: There was a rapid growth in global health education within and beyond CCUGH-affiliated universities with nine universities establishing global health institutes. Translation and definition of global health lacked consistency in Chinese language. Though no course directly related to global health was offered, schools of nursing were gradually participating in global health education and research. Nursing was a critical component of global health, and global health and nursing mutually advanced each other. Nursing education should include global health contents, but at present independent global health curriculum in schools of nursing was not appropriate. Conclusion: Increasingly Chinese universities are promoting global health education through the platform of CCUGH. It is an ideal moment to promote and expand work across the fields of global health and nursing, specifically to highlight opportunities for collaboration across education, research and practice. Keywords: China, Education, Global health, Nursing, Qualitative research